The ghosts of Rome - O'Connor, Joseph 1963- (Harvill Secker, 2025)
February 1944. Six months since Nazi forces occupied Rome. Inside the beleaguered city, the Contessa Giovanna Landini is a member of the band of Escape Line activists known as 'The Choir'. Their mission is to smuggle refugees to safety and help Allied soldiers, all under the nose of Gestapo boss Paul Hauptmann. During a ferocious morning air raid a mysterious parachutist lands in Rome and disappears into the backstreets. Is he an ally or an imposter? His fate will come to put the whole Escape Line at risk. Meanwhile, Hauptmann's attention has landed on the Contessa. As his fascination grows, she is pulled into a dangerous game with him - one where the consequences could be lethal
Keywords: World War, 1939-1945 / Underground movements / Italy / Fiction; Vatican City / History / 20th century / Fiction; Guerre mondiale, 1939-1945 / Mouvements de résistance / Italie / Romans, nouvelles, etc; Suspense fiction; Thriller; Thrillers (Fiction)